(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate sonographic characteristics of ovarian masses and the diagnostic performance of the O-RADS ultrasound lexicon at Hanoi Obstetrics and Gynecology Hospital (2023–2024). Methods: Retrospective cross-sectional study including 384 patients with 420 surgically removed ovarian masses and histopathologic diagnosis. All masses were assigned O-RADS categories based on ultrasound reports. Diagnostic metrics (sensitivity, specificity, PPV, NPV, accuracy) were calculated for different O-RADS thresholds using histopathology as the reference standard. Results: Mean patient age was 33.7 ± 10.8 years; >64% were under 40 years. Of 420 masses, 396 (94.4%) were benign, 10 (2.3%) borderline, and 14 (3.3%) malignant. Most masses were classified as O-RADS 2–3 (93.1%); O-RADS 4: 4.8%; O-RADS 5: 2.1%. Using O-RADS ≥3 yielded 100% sensitivity and 100% NPV but low specificity and PPV. O-RADS ≥4 provided a balanced performance (sensitivity ≈75.0%, specificity ≈97.2%, PPV 62.1%, NPV 98.5%). O-RADS 5 had very high specificity ( 99.7%) and PPV but low sensitivity ( 33.3%). O-RADS ≥ 4 also reduce the frequency of false positive by about 9 times compared to O-RADS ≥ 3 (11 compared to 100) Conclusions: O-RADS ultrasound is a valid and reliable stratification tool in our center. An O-RADS threshold of 4 offers the best trade-off between diagnostic accuracy and clinical relevance for guiding management decisions.